Plan de marketing para mejorar el posicionamiento del comercial y créditos Quillupangui, ubicada en el sector “Pueblo solo Pueblo”, del Distrito Metropolitano de Quito en el período 2015-2016 - Altamirano Tonato, Mayra Rosario (2016)
This research work has the general objective is to improve “the positioning in the market of Quillupangui”. For this reason it is proceeded to develop a situational analysis of the business in which demostrated the SWOT (FODA) process, and through it was possible to identify the main problem that consist is the lack of a strategic planning at medium and long term; also there is an inadequate attention to the customer and also is found that one threats is the growth of its competition. Then it proceeded to perform a market study where several surveys were applied to the unit study that was taken from (PEA) Metropolitan District of Quito for potential customers and for actual customers was taken from the trade center customer base….